2013
DOI: 10.2134/jeq2013.03.0097
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the GRACEnet/REAP Data Contribution, Discovery, and Retrieval System

Abstract: Difficulties in accessing high-quality data on trace gas fluxes and performance of bioenergy/bioproduct feedstocks limit the ability of researchers and others to address environmental impacts of agriculture and the potential to produce feedstocks. To address those needs, the GRACEnet (Greenhouse gas Reduction through Agricultural Carbon Enhancement network) and REAP (Renewable Energy Assessment Project) research programs were initiated by the USDA Agricultural Research Service (ARS). A major product of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…To facilitate those types of activities, site-specific data from which these means were derived are currently being entered into the ARS REAPnet database [24]. The plan for the data contributed to that database is that following peer review and publication, it will be made publically available for further use and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate those types of activities, site-specific data from which these means were derived are currently being entered into the ARS REAPnet database [24]. The plan for the data contributed to that database is that following peer review and publication, it will be made publically available for further use and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated multi-site studies such as USDA-ARS's REAP and greenhouse gas reduction through Agricultural Carbon Enhancement network (GRACEnet) can provide both empirical data as well as soil, weather, and management data required to execute site-specific, regional, and national model simulations. Further, the GRACEnet/REAP data contribution, discovery, and retrieval system provides the capability of running models internally based on associated soils, management, and weather data [109]. The new USDA-ARS LongTerm Agroecosystem Research sites will contribute information as well.…”
Section: System Sustainability and Climate Change Mitigation Potentialmentioning
confidence: 99%
“…3). These decreases in stover biomass yields were less than those associated with a Rayne silt loam in Ohio with 100 % stover removal decreasing the biomass yield after two harvest cycles by roughly 25 % [16]. Further investigation of the ratio of each plant part to the WP revealed that stover removals greater than 50 % decreased the B/WP ratio (bottom to whole plant); conversely, T/WP ratio (top to whole plant) increased with removals approaching 75-100 %; Cob/WP ratio remained relatively steady.…”
Section: Resultsmentioning
confidence: 75%